Wireless sensor network monitoring system: architecture, applications and future directions. (20th September 2019) - Abdelhafidh, Maroua; Fourati, Mohamed; Fourati, Lamia Chaari; Chouaya, Abdessalam
Wireless sensor network monitoring systems (WSNMS) have emerged as one of the most promising research area due to reliable technology progress related to the deployed sensors. This solution is efficiently involved with advanced technologies such as internet of things (IoT) and physical cyber system (CPS) that are designed as a bridge connecting the real world to the digital world. This survey gives a holistic view of WSNMS based on a recent state of the art. We address WSNMS applications and its challenges to facilitate its deployment in real world. We demonstrate the synergy between WSN and the information and communication technologies (ICT) and its major specifications. Finally, we depict open research issues that need to be more studied in the future. We expect to help researchers to get basic knowledge on WSNMS and to open for them new opportunities in regards to understand new technologies considered as an evolution of WSN.